The effect of contextual variables on the attacking style of play in professional soccer - González-Ródenas, J.; Aranda, R.; Aranda-Malaves, R. (Journal of Human Sport & Exercise, 2021)
The aim of this paper was to investigate the interactive effects of contextual variables on the attacking style of play in professional soccer. 5849 team possessions from 40 random matches from Spanish La Liga and English Premier League 2017-2018 were analysed by means of multidimensional observation. Multilevel multivariate logistic regressions showed that home teams had higher odds of implementing fast attacks (p < .05) and lower odds of implementing direct attacks (p < .05) than combinative attacks. High-ranked teams presented lower odds of using direct attacks (p < .05) than combinative attacks in comparison with low-ranked teams, while playing against high-ranked opponents decreased the probability of implementing fast (p < .05) and direct attacks (p < .05) in comparison with low-ranking opponents. As for match status, winning teams presented higher probabilities of attacking by means of counterattacks (p < .001) and direct attacks (p < .001) than combinative attacks compared to losing teams. Finally, playing during the second half presented higher odds of progressing by counterattacks (p < .01) than by combinative attacks. Our results suggest that tactical analysts, coaches and researchers should consider the interactive effects of contextual variables on the teams` style of play when evaluating the offensive performance in professional soccer.